2005
DOI: 10.1007/s10640-004-0758-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Respondent Experience/Knowledge in the Elicitation of Contingent Values: An Investigation of Convergent Validity, Procedural Invariance and Reliability

Abstract: Tests of convergent validity and procedural invariance were used to investigate whether individuals lacking direct experience with a commodity can provide valid responses to contingent-valuation questions eliciting ex post use values. Convergent validity between samples with and without experience was shown to hold for dichotomous-choice responses, but not for open-ended responses. Copyright Springer 2005contingent valuation, dichotomous choice, experience, open-ended, validity, use values,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Dichotomous choice format is also found to provide valid responses despite whether respondents directly experienced the valued commodity or not (McCollum and Boyle 2005). This result is particularly relevant to our study, because our sample did not distinguished between people with and without personal experiences related to each of the air pollution damages.…”
Section: Identifying Protestersmentioning
confidence: 77%
“…Dichotomous choice format is also found to provide valid responses despite whether respondents directly experienced the valued commodity or not (McCollum and Boyle 2005). This result is particularly relevant to our study, because our sample did not distinguished between people with and without personal experiences related to each of the air pollution damages.…”
Section: Identifying Protestersmentioning
confidence: 77%
“…However, our question on WTP refers to a product that is already present in the market and can be understood easily with basic insurance principles. It is well known that familiarity with the proposed good induces wellformed preferences (McCollum & Boyle, 2005). In the case where respondents have little or no experience and knowledge, they may provide invalid responses.…”
Section: On the Determinants Of Wtpmentioning
confidence: 99%
“…The existence of well-formed preferences may be related to respondent's familiarity with, or experience of, the good being valued (Boyle et al, 1993;Roach et al, 1999;Braga and Starmer, 2005;McCollum and Boyle, 2005). Evidence here is mixed.…”
Section: Discussionmentioning
confidence: 88%
“…Evidence here is mixed. Boyle et al (1993) and McCollum and Boyle (2005), when looking at preferences for boating on the Colorado river and moose hunting in Maine, found no significant difference between WTP estimates elicited from more experienced and less experienced respondents. In contrast Roach et al (1993), in a study concerned with boating preferences, found respondents' experience influenced their WTP estimates.…”
Section: Discussionmentioning
confidence: 95%